PENGGUNAAN MODEL PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC (STEM) PADA KONSEP ASAM BASA DI SMAN 1 BAITUSSALAM (Lantanida Journal, 2020)
Based on observations at SMAN 1 Baitussalam, information was obtained that learning outcomes of students on acid-base material were still low, this was caused by the process of learning chemistry that was still teacher-centered and didn’t use specific learning models. The STEM learning model is a One learning model that can be used as  solution to this problem is the learning model of Science, Technology, Engineering, and Mathematics (STEM). The purpose of this study was to obtain information about the effect of the STEM learning model on learning outcomes and student responses, especially on the concept of acid-base in SMAN 1 Baitussalam. This study uses Quasi Experimental design, with data collected through test and questionnaires. Student test results were analyzed using SPSS Version 23.0, where the significance value obtained from the t-test analysis was 0,000